Autonomous agents : from self-control to autonomy - Mele, Alfred R., 1951- (Oxford University Press, 1995)
Alfred Mele examines the concept of self-control on its terms, followed by an examination of its bearing on one's actions, beliefs, and emotions. He considers how, by understanding self-control, man can shed light on autonomous behaviour.
Keywords: Self-control.; Autonomy (Philosophy); Maîtrise de soi.; Autonomie (Philosophie); PHILOSOPHY -- Movements -- Humanism.; Self-control